The Effect of Neuromuscular Training on Mental Health, Depression, and Quality of Life among Older Women: A Randomized Controlled Trial - Ghayour Najafabadi, Mahboubeh; Rahmani, Pooneh; Gharayagh Zandi, Hassan; Nasiri, Ali; Pourreza, Amir; Kelly dos Santos, Isis (Health Nexus, 2026)
The rapid growth of the global aging population has intensified concerns regarding the physical, psychological, and social well-being of older adults, particularly women, as age-related declines in neuromuscular control, balance, and mental health contribute substantially to reduced functional independence and quality of life. Neuromuscular training (NMT) has emerged as a promising multimodal approach to counteract these effects. This study aimed to evaluate the impact of a structured six-week NMT program on mental health, depression, and quality of life in older women. This quasi-experimental study employed a pretest–posttest design with a control group. Thirty women aged 60–70 years were randomly assigned to either an experimental group (n=15) or a control group (n=15). The experimental group participated in an 18-session NMT program over six weeks, while the control group maintained their usual activities. Mental health, depression, and quality of life were measured using the GHQ-28, Beck Depression Inventory-II, and WHOQOL-BREF questionnaires, respectively. Data were analyzed using analysis of covariance (ANCOVA) in SPSS26, with the level of statistical significance set at P0.05), and all ANCOVA assumptions were met. After the intervention, NMT produced significant improvements in mental health (F (1, 27) =7.93, p